Applications of Silver Nanoparticles as Antibiotics for Pathogenic Organisms: Bacteria, Fungi ,Viruses and Algae (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Silver nanoparticles are used in the medical and engineering fields and are still of interest to scientists, possibly due to their small size compared to their efficiency. Previous research has demonstrated the efficacy of silver nanoparticles in inhibiting microbes as they are used as reducing agents. Silver nanoparticles are manufactured in a variety of chemical or physical ways that may have environmental hazards due to their potential toxicity, or they are manufactured in biological, environmentally friendly and non-toxic ways.In this review, we first present the properties of nanoparticles and their synthesis methods and then discuss their role as inhibitors of bacteria, fungi, viruses and algae.